Meningkatkan Motivasi Belajar dengan Model Pembelajaran Problem Based Learning pada Materi Aku Pribadi Yang Unik Kelas X SMA Negeri 1 Gunungsitoli Idanoi - Amonius Halawa; Bonifasius Denny Yuswanto (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
Humans cannot be separated from education. Education is a need that must be fulfilled in human life throughout life. The Pancasila student profile has various competencies which are formulated into six key dimensions. The six dimensions are: Faith, devotion to God Almighty, and noble character, global diversity, mutual cooperation. Independent, critical reasoning, creative. The researcher assumes that to improve optimal learning outcomes in class , able to think to search and find answers to problems given through questions, then this process will develop students' abilities so that they obtain maximum learning outcomes. Researchers conducted classroom action research